Synthesis of Electrospun Polyvinyl Butyral/Bentonite Nanofiber Film for Cationic Dye Removal - Aiizat Ikhwan Abdul Jalil; Syahida Farhan Azha; Adrian Bonilla-Petriciolet; Mohammad Shahadat; Suzylawati Ismail (International Journal of Chemical Engineering)
The textile industry is a common and relevant sector worldwide that generates significant environmental pollution via the discharge of dye-containing wastewater. In this direction, the electrospinning technology can be used to produce adsorbing nanofibers for the treatment of wastewater polluted by dyes and other toxic compounds. The nanofibers obtained by this technology are light and thin, thus providing several advantages (e.g., high surface area) to improve the efficacy of adsorption processes. In this direction, this study reports the preparation of nanofibers from polyvinyl butyral (PVB) and bentonite via electrospinning. This study also reports PVB/bentonite nanofiber mat and its application in adsorbing the cationic dye (methylene blue) from an aqueous solution. The morphology and water contact angles of these nanofibers were analyzed. Results showed that the maximum dye adsorption of these nanofibers was 66.63 mg/g along with 32% removal at pH 9 and 27 ± 2°C. The dye adsorption on these nanofibers was exothermic and pH-dependent, with the best adsorption capacities obtained under alkaline conditions. The adsorption mechanism of this dye molecule on these PVB/bentonite nanofiber mats was associated with van der Waals forces, hydrogen bonding, and electrostatic interactions. This novel composite is an interesting material with improved properties that can be applied to the removal of cationic dyes from wastewater.